ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Expression of HopAI interferes with MAP kinase signalling in Magnaporthe oryzae - Xue Zhang; Wende Liu; Yang Li; Guotian Li; Jin‐Rong Xu (Environmental Microbiology, 2017)
Summary The Pmk1 and Mps1 MAP kinases are essential for appressorium formation and plant infection in Magnaporthe oryzae . However, their exact roles during invasive growth are not clear because pmk1 and mps1 mutants are defective in penetration. To further characterize their functions after penetration, in this study we expressed the Pseudomonas syringae effector HopAI known to inactivate plant MAP kinases in M. oryzae . Constitutive expression of HopAI with the RP27 or TrpC promoter resulted in defects in hyphal growth, conidiation, appressorium penetration and pathogenicity, which is similar to the phenotype of the mps1 mutant. HopAI interacted strongly with Mps1 in vivo and expression of dominant active MKK2 partially suppressed the defects of P RP27 ‐HopAI transformants, which were significantly reduced in Mps1 phosphorylation. When the infection‐specific MIR1 ( Magnaporthe ‐infection‐related gene‐1) promoter was used to express HopAI, P MIR1 ‐HopAI transformants were defective in the spreading of invasive hyphae and elicited strong defense responses in penetrated plant cells. Expression of HopAI in Fusarium graminearum also mainly affected the activation of Mgv1, an Mps1 orthologue. Taken together, our results showed that Mps1 is the major intracellular target of HopAI when it is overexpressed, and MAP kinase signalling is important for cell‐to‐cell movement of invasive hyphae in M. oryzae .

Effects of potassium deficiency on root morphology, ultrastructure and antioxidant enzyme system in sweet potato (Ipomoea batatas [L.] Lam.) during early growth - Ming Liu; Ai-Jun Zhang; Xiao-Guang Chen; Rong Jin; Hong-Min Li; Zhong-Hou Tang (Acta Physiologiae Plantarum, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

NaCl stress induces CsSAMs gene expression in Cucumis sativus by mediating the binding of CsGT-3b to the GT-1 element within the CsSAMs promoter - Li-Wei Wang; Mei-Wen He; Shi-Rong Guo; Min Zhong; Sheng Shu; Jin Sun (Planta, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

MST50 is involved in multiple MAP kinase signaling pathways in Magnaporthe oryzae - Guotian Li; Xue Zhang; Huan Tian; Yoon‐E Choi; W. Andy Tao; Jin‐Rong Xu (Environmental Microbiology, 2017)
Summary Appressorium formation plays a critical role in Magnaporthe oryzae . Mst50 is an adapter protein of the Mst11‐Mst7‐Pmk1 cascade that is essential for appressorium formation. To further characterize its functions, affinity purification was used to identify Mst50‐interacting proteins (MIPs) in this study. Two of the MIPs are Mst11 and Mst7 that are known to interact with Mst50 for Pmk1 activation. Surprisingly, two other MIPs are Mck1 and Mkk2 that are the upstream kinases of the Mps1 pathway. Domain deletion analysis showed that the sterile alpha‐motif of Mst50 but not the Ras‐association domain was important for its interaction with Mck1 and responses to cell wall and oxidative stresses. The mst50 mutant was reduced in Mps1 activation under stress conditions. MIP11 encodes a RACK1 protein that also interacted with Mck1. Deletion of MIP11 resulted in defects in cell wall integrity, Mps1 phosphorylation and plant infection. Furthermore, Mst50 interacted with histidine kinase Hik1, and the mst50 mutant was reduced in Osm1 phosphorylation. These results indicated that Mst50 is involved in all three MAPK pathways in M. oryzae although its functions differ in each pathway. Several MIPs are conserved hypothetical proteins and may be involved in responses to various signals and crosstalk among signaling pathways.

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Protein tyrosine phosphatase 1B expression contributes to the development of breast cancer - Shi-chong Liao; Jin-xin Li; Li Yu; Sheng-rong Sun (Journal of Zhejiang University-SCIENCE B, 2017)

A novel model to assess soil productivity in the dry-hot valleys of China - Xing-wu Duan; Xu Han; Jin-ming Hu; De-tai Feng; Li Rong (Journal of Mountain Science, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The dynamics of landscape-scale ecological connectivity based on least-cost model in Dongshan Island, China - Li-yun Wu; Dong-jin He; Wei-bin You; Zhi-rong Ji; Yong Tan; Li-li Zhao (Journal of Mountain Science, 2017)

Optimized culture medium for the production of flavonoids from Orostachys cartilaginea V.N. Boriss. callus cultures - Wan Bo Zhang; Xuan Chun Piao; Jin Rong Li; Ying Hua Jin; Mei Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)